1994
DOI: 10.1039/an9941901593
|View full text |Cite
|
Sign up to set email alerts
|

Fast determination of aluminium reactive to 1,2-dihydroxyanthraquinone-3-sulfonic acid in sea-water

Abstract: A modification of the method for the determination of aluminium by adsorptive cathodic stripping voltammetry of its 1,2-dihydroxyanthraquinone-3-sulfonic acid (DASA) complex is described. Rapid determination is achieved by using staircase modulation and high potential scan speeds (20 V s-1). Square wave modulation was found inefficient above 2 V s-1 because the potential pulse is distorted by the ohmic drop. The staircase modulation is also distorted, but the determination is not disturbed and high faradaic cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Previous work on the Al-DASA system [5,7] reported that a peak at À 0.8 V was consistently present in stripping voltammograms performed at a HMDE. Furthermore, the current response for this peak is greater than for the peak P4 when analyzed at HMDEs.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Previous work on the Al-DASA system [5,7] reported that a peak at À 0.8 V was consistently present in stripping voltammograms performed at a HMDE. Furthermore, the current response for this peak is greater than for the peak P4 when analyzed at HMDEs.…”
mentioning
confidence: 93%
“…Previous published work showed that the Al/DASA complex is reducible on a HMDE electrode, producing two voltammetric peaks [5,7]. The use of the TMFE was investigated for the electroanalytical determination of aluminum through cathodic stripping voltammetry with DASA.…”
mentioning
confidence: 99%
“…One way to minimize these problems is to use high-frequency square-wave scans, or fast linear-sweep scans [3]. The fast scans tend to lead to increased peak currents, which might then become greater than the interfering capacitance currents, albeit at a loss of resolution for poorly reversible reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum, like alkaline earth and rare earth metal ions, cannot be easily determined by conventional voltammetry because of the difficulty in reducing them at the electrode in aqueous solutions. The development of an adsorptive complex wave relying on the electrochemical responses of organic chelants and/or their "Al-organic ligand complexes" overcame those obstacles [3][4][5]. Chemically modified electrodes, which were prepared by adsorption of dye, were also developed for the determination of aluminum due to their selectivity and simple detection instrumentation [6,7].…”
Section: Introductionmentioning
confidence: 99%